EFFECT OF USING SOME ADDITIVES ON SOME CHEMICAL COMPOSITIONS OF LOCAL BASTURMA DURING STORAGE - Naska A. M. Al-Marazany (Mesopotamia Journal of Agriculture)
The effect of using some food additives like ascorbic acid, nitrate and nitrite , sodium phosphate, lactic acid and acetic acid with different concentrations upon some chemical characteristics of local manufacture basturma during storage within open climate temperature from March to June, was studied. Significant differences were found in the values of the moisture content of different treatments of the stored basturma during storage period. The moisture content of stored basturma decreased simultaneosly with the increase of storage period which led to increase of protein and fat ratio significantly. Treatment with ascorbic acid resulted in the decrease of moisture content and the increase of protein quantity and slight changes in fat content during storage period. An increase in the ratio of protein was appeared when nitrate and nitrite were used. Generally, the use of sodium phosphate led to maintaining of the moisture content of the stored basturma during storage. The treatment with 5% of lactic and acetic acid did not affect significantly on moisture content in comparison with control and significant increase in protein content